Intensive Multimodal Training to Improve Gait Resistance, Mobility, Balance and Cognitive Function in Persons With Multiple Sclerosis: A Pilot Randomized Controlled Trial - Jonsdottir, Johanna; Gervasoni, Elisa; Bowman, Thomas; Bertoni, Rita; Tavazzi, Eleonora; Rovaris, Marco; Cattaneo, Davide (Frontiers in Neurology, 2018)
Persons with multiple sclerosis (MS) have deficits in many aspects of physical and cognitive functioning that can impact on mobility and participation in daily life. The effect of a 4 week intensive multimodal treadmill training on functional mobility, balance, executive functions and participation in persons with MS with moderate to severe disability was investigated. Methods. Thirty eight persons with MS admitted to a rehabilitation center participated in a two arm randomized 2:1 controlled trial. Participants in the experimental group received supervised intensive treadmill training including cognitive and motor dual tasks (DT-group, N=26), 5 sessions per week and a control group received the same amount of supervised strength training (S-group, N=12). The participants were assessed before and after the rehabilitation period with the 2 Minutes Walking Test (2MWT), speed and, static and dynamic balance measures, the Frontal Assessment Battery and the Short Form-12 questionnaire. The main hypothesis was related to the superiority of the treadmill intervention based on a greater proportion of people making a clinically relevant gain (15% increase on 2MWT) in gait resistance following treatment. ANCOVA (Analysis of covariance) models adjusting for baseline measurement of the respective outcome variable, as well as sex, age and EDSS, were used to evaluate differences in efficacy for all variables. P was set at 0.05. Results. Nineteen out of 26 persons in the DT-group made a clinically relevant gain and two out of 12 in the S-Group (P=.001). The DT-group improved more in gait resistance, speed and mobility (P< 0.01). Balance and executive functions instead improved moderately in both groups following training while perception of health remained similar in both groups. Conclusion. A four week multimodal training on treadmill was highly effective in augmenting gait resistance and mobility in moderately to severely affected persons with MS.